The effect of gD-derived peptides on T cell immune response mediated by BTLA-HVEM protein complex in melanoma patients - Wojciechowicz, Karolina; Kuncewicz, Katarzyna; Rutkowski, Jacek; Jassem, Jacek; Wardowska, Anna; Spodzieja, Marta (Frontiers in Immunology, 2024)
The effector function of T cells is regulated via immune checkpoints, activating or inhibiting the immune response. The BTLA-HVEM complex, the inhibitory immune checkpoint, may act as one of the tumor immune escape mechanisms. Therefore, interfering with the binding of these proteins can prove beneficial in cancer treatment. Our study focused on peptides interacting with HVEM in the same place as BTLA, thus disrupting the BTLA-HVEM interaction. These peptides' structure and amino acid sequences are based on the gD protein, the ligand of HVEM. Here, we investigated their immunomodulatory potential in melanoma patients. Flow cytometry analyses of activation, proliferation, and apoptosis of T cells from patients were performed. Additionally, we evaluated changes within the T cell memory compartment. The most promising compound – Pep(2), increased the percentages of activated T cells and promoted their proliferation. Additionally, this peptide affected the proliferation rate and apoptosis of melanoma cell line in co-culture with T cells. We conclude that the examined peptide may act as a booster for the immune system. Moreover, the adjuvant and activating properties of the gD-derived peptide could be used in a combinatory therapy with currently used ICI-based treatment. Our studies also demonstrate that even slight differences in the amino acid sequence of peptides and any changes in the position of the disulfide bond can strongly affect the immunomodulatory properties of compounds.